Multi-Agent Based E-Social Care Support System for Inhabitancies of a Smart Eco-Social Apartment - Bielskis, A. A.; Andziulis, A.; Ramasauskas, O.; Guseinoviene, E.; Dzemydiene, D.; Gricius, G. (Elektronika ir Elektrotechnika, 2011)
The paper presents further development steps of recently proposed model of an adaptive multi-agent-based e-social care system by introducing in it an intelligent power controller to supporting people in a Smart Ecological and Social Apartment, the SESA. The schematic diagrams of the controller are proposed for adaptive control of motors and LED lights as well as for measurements of EDA, HR, and FT signals of inhabitancies in the SESA. The proposed in this paper multi-agent system consists of two groups of agents, first, the agents for human’s physiological data collection, analysis and emotional state detection, and, second, the agents for an intelligent power control which takes environmental and hardware parameters and, with the use of embedded agents, provides adaptive control of LED lights, temperature as well as of power consuming by motors used in the SESA in accordance with the human state defined by the first group of agents.